How Public Trust Matters to Future Taxpayer Compliance in Indonesia - Shelvi, Shelvi; Rachmawati, Tutik (UI Scholars Hub, 2026)
This study examines the role of public trust in shaping future taxpayer compliance, a critical factor for achieving the long-term development vision of Indonesia Emas 2045. While trust has been extensively studied in the context of current taxpayers, research on its role among younger generations as future taxpayers in developing economies remains limited. To address this gap, a mixed-methods approach was employed, combining survey data from 420 students with in-depth interviews. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypothesis that public trust influences future taxpayer compliance. The results demonstrate that public trust has a strong and significant effect on taxpayer compliance intention (β = 0.533, p < 0.001), explaining nearly 28% of the variance in compliance behavior. Although trust in individual leaders, such as the president, is relatively high, concerns over corruption, unequal welfare distribution, and weak institutional legitimacy reduce overall trust in the tax system. Qualitative findings further reveal skepticism among the younger generation regarding the fairness and effectiveness of tax allocation. These findings highlight the importance of enhancing policy transparency, strengthening oversight mechanisms, reducing inequality, and integrating civic education to foster tax morale. Building institutional trust is thus crucial to secure sustainable tax compliance among future taxpayers in Indonesia.